From Policy to Practice: The State of E-Governance in Nepal - Ghimire, Dipesh Kumar (Dhaulagiri Journal of Sociology and Anthropology, 2025)
E-Governance has emerged as a transformative tool to enhance democratic governance, transparency, accountability, and inclusive service delivery. This paper critically examines the evolution, status, challenges, and opportunities of e-governance in Nepal, drawing on policy documents, academic literature, and reports from bilateral agencies and civil society organizations. The study assesses how digital governance initiatives, such as the e-Government Master Plan 2006, the Digital Nepal Framework 2019, and the 16th Five-Year Plan, have shaped the country’s digital trajectory. While significant progress has been made in digital service adoption and citizen engagement, strengthened by expanding telecom infrastructure and the COVID-19 pandemic, Nepal’s E-Governance landscape remains constrained by inadequate human capital, digital divides, weak political will, poor implementation mechanisms, and infrastructural deficits. This review aims to contribute to ongoing discourse by identifying policy gaps, stakeholder engagement needs, and strategies to mainstream E-Governance into Nepal’s democratic and socio-economic development processes. This study employs a desk review methodology to synthesize diverse secondary sources and examine the existing policy framework on e-governance in Nepal. The findings show significant progress through initiatives such as the e-Government Master Plan, the Digital Nepal Framework, and expanded digital service delivery across the country. However, full implementation remains constrained by digital divides, weak infrastructure, socio-political barriers, limited skilled human resources, and low public awareness. Finally, this article underscores the potential of E-Governance to catalyze inclusive development and democratic deepening in Nepal.